(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents the result of treatment of a child with prolonged neonatal hyperbilirubinemia on the background of neonatal pneumonia and atrial septal defect of the heart. In this clinical case the child was hospitalized in the Samarkand branch of the Republican Scientific Center of Emergency Medical Care due to hectic temperature and signs of acute inflammatory process. During the examination the child in the background of prolonged hyperbilirubinemia was diagnosed pneumonia and a defect of the atrial septal defect of the heart . During the treatment of this patient the treatment algorithm was clearly chosen due to the existing pathology of the child. The treatment was based on pathophysiological aspects and coordinated on the anatomical and physiological characteristics of this child.